Physical condition, social isolation, and family relationship quality as predictors of parental well-being and psychological distress in indonesian stunting households: a PLS-SEM Analysis - Indah Sukmawati; Afdal Afdal; Denia Syapitri; Miftahul Fikri; Gusni Dian Suri (Journal of Counseling, Education and Society, 2025)
Parents of children with stunting face persistent caregiving stressors associated with elevated psychological distress, yet the well-being mechanisms through which these stressors operate remain underspecified. Drawing on Conservation of Resources (COR) theory and Bronfenbrenner's ecological systems framework, this study examined physical condition, family relationship quality, and social isolation as antecedents of parental well-being, and tested well-being as a mediator of psychological distress in Indonesian caregiving households. A cross-sectional, explanatory design was employed with 284 parents (Mage = 32.8 years, SD = 5.3; 86.62% mothers) from three provinces with elevated stunting prevalence in Indonesia. Physical condition and social isolation were significant predictors of parental well-being, while family relationship quality was non-significant. Well-being was strongly associated with parental psychological distress and mediated the effects of physical condition and social isolation, but not family relationship quality. These findings suggest that somatic resource depletion and social exclusion are more strongly associated with parental well-being than perceived family relationship quality in this context. Well-being appears to function as the central pathway linking contextual stressors to psychological distress, highlighting the importance of integrated stunting intervention programmes that address parental physical health and social connectedness.